Pengaruh Remunerasi dan Supervisor Support Terhadap Turnover Intention Karyawan PT Makanan Asli Indonesia - Latifani, Arda Aprilia; Muhyidin, Ayi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effect of remuneration and supervisor support on employee turnover at PT Makanan Asli Indonesia. Based on the results of the analysis, it was found that remuneration has a negative and significant effect on employee turnover. This shows that a competitive and fair remuneration system can effectively reduce employee intentions to leave the company. Remuneration that includes salary, incentives, benefits, and other forms of compensation provides rewards for employee contributions, meets their basic needs, and increases job satisfaction, thereby strengthening loyalty to the company. In contrast, supervisor support does not have a significant effect on turnover intentions. Supervisor support in the form of communication, attention to employee needs, or appreciation for their contributions, although important, is not strong enough to influence employee intentions to stay. This shows that other factors, such as remuneration or work culture, are more dominant in influencing turnover intentions.